Effects of enzyme replacement therapy for cardiac-type Fabry patients with a Chinese hotspot late-onset Fabry mutation (IVS4+919G>A). Issue 7 (16th July 2013) - Lin, Hsiang-Yu; Liu, Hao-Chuan; Huang, Yu-Hsiu; Liao, Hsuan-Chieh; Hsu, Ting-Rong; Shen, Chia-I; Li, Shao-Tzu; Li, Cheng-Fang; Lee, Li-Hong; Lee, Pi-Chang; Huang, Chun-Kai; Chiang, Chuan-Chi; et al.
Abstract : Objective: Current studies of newborn screening for Fabry disease in Taiwan have revealed a remarkably high prevalence of cardiac-type Fabry disease with a Chinese hotspot late-onset Fabry mutation (IVS4+919G>A). Design: Retrospective cohort study. Setting: Tertiary medical centre. Participants: 21 patients with cardiac-type Fabry disease (15 men and 6 women) as well as 15 patients with classic Fabry disease (4 men and 11 women) treated with biweekly intravenous infusions of agalsidase β (1 mg/kg) or agalsidase α (0.2 mg/kg) for at least 6 months. Outcome measures: These data were collected at the time before enzyme replacement therapy (ERT) began and followed up after ERT for at least 6 months, including patient demographics, medical history, parameter changes of cardiac status and renal functions, plasma globotriaosylsphingosine (lyso-Gb3) and Mainz Severity Score Index. Results: After 6–39 months of ERT, plasma lyso-Gb3 was found to be reduced in 89% (17/19) and 93% (14/15) of patients with cardiac-type and classic Fabry disease, respectively, which indicated an improvement of disease severity. For patients with cardiac-type Fabry disease, echocardiography revealed the reduction or stabilisation of left ventricular mass index (LVMI), the thicknesses of intraventricular septum (IVS) and left posterior wall (LPW) in 83% (15/18), 83% (15/18) and 67% (12/18) of patients, respectively, as well as 77% (10/13), 73% (11/15) and 60% (9/15) for those with classic type. Most patients showed stable renal function after ERT. There were statistically significant improvements (p<0.05) between the data at baseline and those after ERT for values of plasma lyso-Gb3, LVMI, IVS, LPW and Mainz Severity Score Index. No severe clinical events were reported during the treatment. Conclusions: ERT is beneficial and appears to be safe for Taiwanese patients with cardiac-type Fabry disease, as well as for those with the classic type.